ln(6x-3)+3=10

Simple and best practice solution for ln(6x-3)+3=10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(6x-3)+3=10 equation:


Simplifying
ln(6x + -3) + 3 = 10

Reorder the terms:
ln(-3 + 6x) + 3 = 10
(-3 * ln + 6x * ln) + 3 = 10
(-3ln + 6lnx) + 3 = 10

Reorder the terms:
3 + -3ln + 6lnx = 10

Solving
3 + -3ln + 6lnx = 10

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3ln + -3 + 6lnx = 10 + -3

Reorder the terms:
3 + -3 + -3ln + 6lnx = 10 + -3

Combine like terms: 3 + -3 = 0
0 + -3ln + 6lnx = 10 + -3
-3ln + 6lnx = 10 + -3

Combine like terms: 10 + -3 = 7
-3ln + 6lnx = 7

Reorder the terms:
-7 + -3ln + 6lnx = 7 + -7

Combine like terms: 7 + -7 = 0
-7 + -3ln + 6lnx = 0

The solution to this equation could not be determined.

See similar equations:

| 5x-27=6y | | 2/x+3-1/2=3 | | 4x/2x^-1/2 | | x=-3y+8 | | 4y^2+16y+2x+10=0 | | 2x+2y=310 | | y=ln(sinx) | | 8x+4y+9x= | | 12x+8=-4 | | 4y^2+16y+2+10=0 | | 3(2x+3)-5(7-4x)-2(5x+4)=-2 | | -5x/4=12 | | y=7/4x-2 | | 225=16x+x^2 | | -2w-22=3(w-4) | | (-5/4)x=12 | | 4x+8-9x=16-19x+14x-8 | | 4d-7=35 | | 6x+3-9=0 | | x+7900=13220 | | y=-4/3(-3)+4 | | sinv=0.26 | | 6m^2-3=9 | | 8m+3n-2m+7n= | | -13=-6x-10 | | x-2/5x-2/5x-5=15 | | -6r^2=-276 | | 8m+3n-2m=7n | | -6x^2=126 | | y+1.05=7.36 | | 3x1/10 | | y^2+4=12 |

Equations solver categories